2015
DOI: 10.1002/btpr.2077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leaf incubation temperature profiles on agrobacterium tumefaciens‐mediated transient expression

Abstract: Agrobacterium tumefaciens-mediated transient expression is known to be highly dependent on incubation temperature. Compared with early studies that were conducted at constant temperature, we examined the effect of variable leaf incubation temperature on transient expression. As a model system, synthetic endoglucanase (E1) and endoxylanase (Xyn10A) genes were transiently expressed in detached whole sunflower leaves via vacuum infiltration for biofuel applications. We found that the kinetics of transient express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…R 2 = 0.83). The highest levels of recombinant protein were achieved at an OD 600 nm of 0.85 (Figure A), which was consistent with previous reports of transient expression mediated by A. tumefaciens in the absence of silencing inhibitors …”
Section: Resultssupporting
confidence: 92%
“…R 2 = 0.83). The highest levels of recombinant protein were achieved at an OD 600 nm of 0.85 (Figure A), which was consistent with previous reports of transient expression mediated by A. tumefaciens in the absence of silencing inhibitors …”
Section: Resultssupporting
confidence: 92%
“…For example, Duncan grapefruit exhibited a higher efficiency of genetic transformation than trifoliate orange and a lower efficiency of transient gene expression. Jung et al (2015) suggested that the overall level of transient gene expression is determined by protein synthesis in addition to T-DNA transfer, which determines the genetic transformation efficiency. Thus, the consistency observed in the research of Bhaskar et al (2009) may not be absolute between the transient expression efficiency and genetic transformation efficiency causing by plant genotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, air temperature may not necessarily have to be maintained constant. Jung et al ( 2015 ) recently explored the effects of two-phase air temperature control. They observed fivefold higher content of recombinant xylanase in detached sunflower leaves treated at 20°C for the first 4 days postinoculation followed by 27°C for 2 days than that of leaves exposed to a constant temperature of 20°C.…”
Section: Effects Of Postinoculation Environmental Factorsmentioning
confidence: 99%
“…It may then be better to shift the temperature to a higher level optimal for subsequent recombinant protein accumulation and be maintained at the level for the remaining period. The result of Jung et al ( 2015 ) illustrates the usefulness of the dynamic control of air temperature as a strategy to improve recombinant protein accumulation.…”
Section: Effects Of Postinoculation Environmental Factorsmentioning
confidence: 99%